AMOBILISASI SEL Bacillus licheniformis KA-08 DALAM MENGHASILKAN KERATINASE TERMOSTABIL - Anthoni Agustien (The East Java Biological Society, 2011)
Isolate local Bacillus licheniformis KA-08 known extracellular thermostable keratinase producers. Scale up of thermostable keratinase production can be with cells immobilized. The objective of the research is to thermostable keratinase production of B. licheniformis KA-08 cells immobilization. Thermostable keratinase activities were determined with modification of Brandelli and Riffel method. Protein concentration of enzyme determined with Lowry method. Immobilization of cells by Ca-alginate matrix with Adinarayana method, alginate concentration and amount of alginate bead effects with Beshay method. The result extracellular thermostable keratinase of B. licheniformis KA-08 cells immobilized was maximum produced at 12 times incubation with activity as 9.25 U/mg. Three percent alginate has optimum activity. Three hundred alginate beads has optimum activity. Cells immobilized of B. licheniformis KA-08 has scale up of thermostable keratinase activity at 2 times than free cells. Thermostable keratinase produced by cell immobilized was nine cycles.